Impact Media to take off and when the special gifts in Baghdad for a period of 555-656h / 1160-1258 - زينب محمد طه (College of Education for Women, 2019)
The dislocation and gifts at special is the aspect of social life they reflect us how rich and influential class of society, a special category of the ruling category of the caliph and his family and his ministers and his generals and senior statesmen, a powerful and wealth and power and study here dealing with the effect the media for the distribution of dislocations and gifts to the special category both internally and for employers the state and its men or externally represented foreign relations with princes in the state and the regions and include the definition of the concepts above with surrounding contents and events distributed as the some of which were distributed in certain occasions fixed times while others did not have a specific time, either on the effect the media how to give it a big effect on the hearts of those who were accompanying dislocation as manifestations of big media and celebration, as well as the main findings of the study.